Association between albumin to globulin ratio and all-cause and cardiovascular mortality among individuals with cardiovascular-kidney-metabolic syndrome: results from NHANES 2003 to 2018 - Wang, Guangyu; Li, Guangyu; Wang, Pengfei; Zang, Minhua; Pu, Jun (Frontiers in Nutrition, 2025)
ObjectiveThe albumin-to-globulin ratio (AGR) is a promising biomarker for inflammation and nutritional status. However, its association with mortality in individuals with Cardiovascular-Kidney-Metabolic (CKM) syndrome remains underexplored. This study investigates the relationship between AGR and mortality outcomes in CKM syndrome, aiming to provide insights for risk assessment and management in this population.MethodsWe conducted a cohort study utilizing data from the National Health and Nutrition Examination Survey (NHANES) 2003–2018, with mortality follow-up through 31 December 2019. Survey-weighted multivariable Cox hazards regression models assessed the associations between AGR and all-cause and cardiovascular disease (CVD) mortality. Nonlinear relationships and threshold effects were evaluated using smooth curve fitting and piecewise linear regression. Sensitivity analyses, subgroup analyses, and interaction tests were further performed to validate the findings.ResultsOver a median follow-up of 8.33 years, 1,745 all-cause deaths occurred, including 534 CVD-related deaths. After multivariable adjustment, a significant inverse dose–response relationship was observed between AGR and both all-cause and CVD mortality. Specifically, a nonlinear association was identified for all-cause mortality, with an inflection point at an AGR of 1.26, whereas the relationship with CVD mortality remained linear. Compared with the lowest AGR quartile, individuals in the highest AGR quartile had multivariable-adjusted hazard ratios (HR) of 0.55 (95% CI: 0.45–0.67) for all-cause mortality and 0.47 (95% CI: 0.34–0.64) for CVD mortality (P trend < 0.0001 for both outcomes). Each one-unit increase in AGR was associated with a 62% reduction in the risk of all-cause death and a 73% reduction in the risk of CVD mortality. The inverse association with all-cause mortality was more pronounced among individuals under 60 years, daily smokers, Mexican Americans and those in CKM stage 1, while the association with CVD mortality was stronger among individuals with a college degree, those under 60 years, and daily smokers. Sensitivity analyses confirmed these findings.ConclusionHigher AGR is significantly associated with reduced risks of both all-cause and CVD mortality in the CKM syndrome population. Notably, while the relationship with all-cause mortality is nonlinear, the association with CVD mortality follows a linear pattern. These findings suggest that AGR could serve as a valuable biomarker for mortality risk stratification in CKM syndrome.